Beach carrying capacity management under Covid-19 era on the Basque Coast by means of automated coastal videometry. (1st July 2021) - Epelde, Irati; Liria, Pedro; de Santiago, Iñaki; Garnier, Roland; Uriarte, Adolfo; Picón, Artzai; Galdrán, Adrián; Arteche, Jose Antonio; Lago, Alberto; Corera, Zurik; Puga, Iñaki; Andueza, Jose Luis; et al.
Abstract: This paper describes the methodology followed to implement social distancing recommendations in the COVID-19 context along the beaches of the coast of Gipuzkoa (Basque Country, Northern Spain) by means of automated coastal videometry. The coastal videometry network of Gipuzkoa, based on the KostaSystem technology, covers 14 beaches, with 12 stations, along 50 km of coastline. A beach user detection algorithm based on a machine learning approach has been developed allowing for automatic assessment of beach attendance in real time at regional scale. For each beach, a simple classification of occupancy (low, medium, high, and full) was estimated as a function of the beach user density (BUD), obtained in real time from the images and the maximum beach carrying capacity (BCC), estimated based on the minimal social distance recommended by the authorities. This information was displayed in real time via a web/mobile app and was simultaneously sent to beach managers who controlled the beach access. The results showed a strong receptivity from beach users (more than 50.000 app downloads) and that real time information of beach occupation can help in short-term/daily beach management. In the longer term, the analysis of this information provides the necessary data for beach carrying capacity management and can help the authorities in controlling and in determining their maximum capacity. Highlights: Coastal videometry is used for beach carrying capacity management under COVID-19. A beach user detection algorithm based on a machine learning approach is applied on a regional videometry network. Real-time beach information is sent to beach managers and users through a web/mobile app. Remarkable changes in user's attendance and behaviour have been detected during 2020.